2020
DOI: 10.18632/aging.103776
|View full text |Cite
|
Sign up to set email alerts
|

Vascular, inflammatory and metabolic risk factors in relation to dementia in Parkinson’s disease patients with type 2 diabetes mellitus

Abstract: There are limited data on vascular, inflammatory, metabolic risk factors of dementia in Parkinson’s disease (PD) with type 2 diabetes mellitus (DM) (PD-DM). In a study of 928 subjects comprising of 215 PD with DM (including 31 PD-DM with dementia, PD-DMD), 341 PD without DM (including 31 PD with dementia, PDD) and 372 DM without PD (including 35 DM with dementia, DMD) patients, we investigated if vascular, inflammatory, metabolic, and magnetic resonance imaging (MRI) markers were associated with dementia in PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…Recently, some studies (Ren et al, 2017 ; Cui et al, 2019 ) have also combined TMS with neuroimaging and genetic approaches to further understand the potential mechanisms underlying the rTMS effects on cognition. The default mode network (DMN), serum lipid levels (such as cholesterol and triglyceride levels) (Weng et al, 2018 ; Wang et al, 2020a ; Yang et al, 2020 ), and oxidative stress (such as superoxide dismutase) (Zhu et al, 2019 ) have been reported to play critical roles in modulating cognitive function in age-related neurodegenerative diseases. Cui et al ( 2019 ) showed that rTMS-induced hypoconnectivity within DMN was associated with clinical cognitive improvements in patients with amnestic MCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some studies (Ren et al, 2017 ; Cui et al, 2019 ) have also combined TMS with neuroimaging and genetic approaches to further understand the potential mechanisms underlying the rTMS effects on cognition. The default mode network (DMN), serum lipid levels (such as cholesterol and triglyceride levels) (Weng et al, 2018 ; Wang et al, 2020a ; Yang et al, 2020 ), and oxidative stress (such as superoxide dismutase) (Zhu et al, 2019 ) have been reported to play critical roles in modulating cognitive function in age-related neurodegenerative diseases. Cui et al ( 2019 ) showed that rTMS-induced hypoconnectivity within DMN was associated with clinical cognitive improvements in patients with amnestic MCI.…”
Section: Discussionmentioning
confidence: 99%
“…Along with cognitive decline, MCI implies an increased risk of falls, slow walking speed, and physical frailty (LeWitt et al, 2020 ; Ma and Chan, 2020 ). The mechanisms underlying cognitive decline are multifactorial, including inflammation, impaired hypothalamic-pituitary axis stress response, imbalanced energy metabolism, mitochondrial dysfunction, oxidative stress, and endocrine dysfunction (Zou et al, 2018 ; Xu et al, 2019a ; Li et al, 2020 ; Ma and Chan, 2020 ; Wang et al, 2020a ). The annual conversion rate of MCI to dementia ranges from 10 to 15%, demonstrating that it is an important condition to identify and treat (Petersen et al, 2009 ; Ding et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A range of mechanisms are involved in the pathogenesis of synucleinopathies, including oxidative stress, neuroinflammation and mitochondrial dysfunction (Blandini, 2013;Xu et al, 2019;Yang et al, 2020). Among them, inflammation has been recognized as the key factor (Wang et al, 2020;Zheng et al, 2020). Kishimoto et al (2019) revealed that gut microbiota changes were associated with intestinal inflammation, which may contribute to α-synuclein misfolding (Zheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease patients frequently suffer from mild cognitive impairment (MCI) (MoCA score more than 21 and less than 26) (Litvan et al, 2012), who are at higher risk of developing dementia compared to PD patients with normal cognition (PD-NC) (Kehagia et al, 2010). Several lines of evidence suggested the inflammatory risk factors (Trefoil Factor 3,neutrophils,lymphocytes,et al) in PD may modulate underlying neurodegeneration particularly in relation to dementia (Stojkovic et al, 2018;Zou et al, 2018;Nicoletti et al, 2020;Wang et al, 2020). It is promising to detect MRI-visible EPVS burden as a marker of cognitive decline in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Significant correlations between TFF3/ChE activity/Hcy levels and PDD/VPD severities were found, including motor dysfunction, declining cognition, and mood/gastrointestinal symptoms (Zou et al, 2018 ). To explore the vascular, inflammatory, metabolic risk factors of dementia in PD with type 2 diabetes mellitus (DM) (PD-DM), lower LDL, and higher fibrinogen were the most significant risk factors in PD-DM with dementia (Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%